Association of Seizure, Facial Dysmorphism, Congenital Umbilical Hernia and Undescended Testes - Thapa, LI; Pokharel, BR; Paudel, R; Rana, PVS (Kathmandu University Medical Journal, 2012)
With the advances in neurogenetics association of epilepsy and intellectual disability with chromosomal abnormalities are being increasingly recognized. While onset of seizures with mental retardation at an early age indicate chromosomal abnormality, combination of characteristics facial dysmorphism and congenital abnormalities gives a clue of a particular syndrome. In addition MRI findings may help in confirming the diagnosis. A nine years old boy is presented where early onset seizure, mental retardation, delayed development of speech, presence of facial dysmorphism, umbilical hernia and undescended testes suggested possibility of chromosomal 6q deletion disorder. Important deletion disorders are discussed and importance of clinical examination is stressed. KATHMANDU UNIVERSITY MEDICAL JOURNAL VOL.10 | NO. 1 | ISSUE 37 | JAN - MAR 2012 | 91-93 DOI: http://dx.doi.org/10.3126/kumj.v10i1.6924